2018
DOI: 10.1590/1678-5150-pvb-5400
|View full text |Cite
|
Sign up to set email alerts
|

Controle de parasitas gastrintestinais em ovinos e análise financeira de uma fazenda com sistema de pastejo rotacionado irrigado no semiárido nordestino

Abstract: RESUMO: O sistema de pastejo rotacionado irrigado é uma alternativa para a ovinocultura do semiárido. No entanto, a maior limitante para sua implementação são as dificuldades para controlar as parasitoses gastrintestinais. Neste trabalho objetivou-se determinar medidas de manejo para o controle das helmintoses gastrintestinais de ovinos em pastejo rotacionado irrigado e fazer a análise econômica do sistema. O experimento foi realizado em uma fazenda no Munícipio de Belém do São Francisco, Pernambuco, no períod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
5
1
3
Order By: Relevance
“…The annual costs for the creation of the goats recorded in this study corroborate with several authors (Dal Monte et al, 2010;Barros et al, 2015;Carvalho et al, 2011;Pinto et al, 2014;Stivari et al, 2014), which observed that, among the items that make up the costs of production of ruminants, in a general way, the costs of supply is the item of greatest impact on the total cost of production. One of the major obstacles of the dairy goat farming is, without a shadow of a doubt, the high mortality with diseases that affect the flock (Vieira et al, 2018). However, one must emphasize that the two systems evaluated, the costs with animal remained below 1.5% of all capital needed to maintain the 72 dairy goats, showing that despite the great health difficulty found by goat farmers, expenditure on medicines and health treatments proved to be a small portion of annual costs.…”
Section: Resultsmentioning
confidence: 94%
“…The annual costs for the creation of the goats recorded in this study corroborate with several authors (Dal Monte et al, 2010;Barros et al, 2015;Carvalho et al, 2011;Pinto et al, 2014;Stivari et al, 2014), which observed that, among the items that make up the costs of production of ruminants, in a general way, the costs of supply is the item of greatest impact on the total cost of production. One of the major obstacles of the dairy goat farming is, without a shadow of a doubt, the high mortality with diseases that affect the flock (Vieira et al, 2018). However, one must emphasize that the two systems evaluated, the costs with animal remained below 1.5% of all capital needed to maintain the 72 dairy goats, showing that despite the great health difficulty found by goat farmers, expenditure on medicines and health treatments proved to be a small portion of annual costs.…”
Section: Resultsmentioning
confidence: 94%
“…Em relação as infecções simultâneas com vários gêneros, como foi observado no presente estudo, também tem sido citadas por vários autores, sendo os rebanhos acometidos pela maioria das vezes por infecções mistas, o Haemonchus é o gênero de maior prevalência correspondendo a níveis superiores a 80% nas cargas parasitárias dos pequenos ruminantes, podendo estar presente no rebanho durante todo o ano, sendo responsável pela enfermidade hemoncose (AMARANTE; OLIVEIRA, 2007). No presente estudo, como pode ser observado na Tabela 2, houve predominância de larvas infectantes gênero Haemonchus, o que também tem sido observado pelos autores Domingues et al (2013); Vieira et al (2018); Biolchi; Pedrassani (2019); Ferraz et al (2019); Toscano et al (2019), que afirmaram ser a espécie mais patogênica e relativamente comum de helmintos em áreas tropicais e subtropicais, onde no verão ocorrem temperaturas amenas e altos índices de chuva. A Moniezia é um cestódeo de distribuição mundial, podendo levar a perdas significativas na ovinocultura quando em alto grau de infecção.…”
Section: Resultsunclassified
“…One of the great obstacles for producing lambs is the high mortality from diseases that affect the herd (Vieira et al, 2018). However, animal health costs were below 1% of the capital required to maintain the 468 Morada Nova lambs within a year, which shows that despite the great health difficulty faced by lamb producers, drug and treatment expenses represented just a small portion of annual costs.…”
Section: Resultsmentioning
confidence: 99%